Determinan Belanja Kesehatan Rumah Tangga di Pulau Jawa Menggunakan Geographically Weighted Regression - Fadhila, Yaulanda; Projo, Nucke Widowati Kusumo (Jurnal Ekonomi Kesehatan Indonesia, 2024)
The success of a country’s health development is marked by achieving fair access to healthcare and protecting the population from financial risks of health. Household spending on healthcare, or out-of-pocket (OOP) expenses, in Indonesia, remains far above the ideal limit set by the WHO. There is a noticeable disparity in OOP health expenditures across provinces in Indonesia. The five provinces with the highest per capita OOP expenses are on Java island. This high per capita OOP spending on Java indicates potential issues with access to healthcare services and financial protection in this region. This study aims to identify factors influencing household OOP health expenditures by considering regional effects in Java. The research utilizes secondary data from the 2022 National Socio-Economic Survey (Susenas) and data from BPS publications. The method used is spatial analysis with geographically weighted regression (GWR). The results indicate that all study variables affect household OOP health expenditures in Java’s districts and cities. Life expectancy, average years of schooling, transportation expenses to health facilities, the doctor-to-population ratio per 1,000 people, and the percentage of inpatient cases positively correlate with household OOP health spending. The variables of health insurance ownership percentage and poverty rate negatively correlate with household OOP health expenditures in each district and city in Java. However, the significance of local coefficients shows variation in the number of towns and neighborhoods for each variable. Thus, different variables influence each district and city on Java.